If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -1x = 12 + -5x Solving 9 + -1x = 12 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 9 + -1x + 5x = 12 + -5x + 5x Combine like terms: -1x + 5x = 4x 9 + 4x = 12 + -5x + 5x Combine like terms: -5x + 5x = 0 9 + 4x = 12 + 0 9 + 4x = 12 Add '-9' to each side of the equation. 9 + -9 + 4x = 12 + -9 Combine like terms: 9 + -9 = 0 0 + 4x = 12 + -9 4x = 12 + -9 Combine like terms: 12 + -9 = 3 4x = 3 Divide each side by '4'. x = 0.75 Simplifying x = 0.75
| 5x^2+30-60=0 | | 5x^2+1-246=0 | | 5(x+y)=zforx | | 9-c=12-5c | | f(x)=x^2-10x+98 | | 5x^2+26-24=0 | | Y=8/9x-4 | | 9x-1=107 | | x^3+3x-2=0 | | 7[4-(3-5x)]+x=4(9x+2)-1 | | -10x+3(x-4)+6x=5x-48 | | 2-6=36x-5 | | x-2+x+3=3x-4 | | x(5x+7)=2x^2-9x+64 | | 15x-60=-12x-54 | | -[4z-(9z+8)]=8+(4z+6) | | 3x^9/2x^5 | | 10+6r=104 | | 8a-2a+12=10a-4 | | 10-6r=104 | | 10a-22=13a+5 | | 15=6-2a | | 7+1=7x-11 | | 4a+18=2a-26 | | 1=(x+1)ln(x+1)+xln(x) | | 2x-3=10x+19 | | 3D+2W=18 | | y+1(9+24)-21=21 | | 3xy-2x+4= | | 12a/8/5 | | 6x+2=2x+18 | | 5g+7g=10g |